Direct Interaction between Calmodulin and the Grb7 RA-PH Domain - Watson, Gabrielle M.; Wilce, Jacqueline A. (International journal of molecular sciences, 2020)
Grb7 is a signalling adapter protein that engages activated receptor tyrosine kinases at cellular membranes to effect downstream pathways of cell migration, proliferation and survival. Grb7’s cellular location was shown to be regulated by the small calcium binding protein calmodulin (CaM). While evidence for a Grb7/CaM interaction is compelling, a direct interaction between CaM and purified Grb7 has not been demonstrated and quantitated. In this study we sought to determine this, and prepared pure full-length Grb7, as well as its RA-PH and SH2 subdomains, and tested for CaM binding using surface plasmon resonance. We report a direct interaction between full-length Grb7 and CaM that occurs in a calcium dependent manner. While no binding was observed to the SH2 domain alone, we observed a high micromolar affinity interaction between the Grb7 RA-PH domain and CaM, suggesting that the Grb7/CaM interaction is mediated through this region of Grb7. Together, our data support the model of a CaM interaction with Grb7 via its RA-PH domain.